Alexander von Humboldt’s contribution to the biomedical sciences and scientific illustration. In observation of his 250th anniversary - Magurean, Irina Dora; Dumitrascu, Dan L. (Medicine and Pharmacy Reports, 2020)
Alexander von Humboldt (1769-1859) is one of the most prominent Germans. His multidisciplinary activity set standards to science at the beginning of modern era. His personality is celebrated worldwide. The Alexander von Humboldt Foundation in Bonn is still preserving his memory and endorsing research in all the fields. This paper is a historical sketch presenting his contributions to the development of medical sciences and also to the progress of scientific illustrations. We also introduce personalities of the Cluj-Napoca medical school who were fellows of the Alexander von Humboldt Foundation.